Depression screening in cognitively normal older adults: Measurement bias according to subjective memory decline, brain amyloid burden, cognitive function, and sex. Issue 1 (28th September 2020) - Thompson, Louisa I.; Jones, Richard N.
Abstract: Introduction: Understanding the associations among depression, subjective cognitive decline, and prodromal Alzheimer's disease (AD) has important implications for both depression and dementia screening in older adults. The Geriatric Depression Scale (GDS) is a depression screening tool for older adults that queries memory concerns. To determine whether depression symptoms on the GDS (15‐item version), including self‐reported memory problems, differ by levels of brain amyloid beta (Aβ), a pathological hallmark of early stage AD, we investigated potential measurement bias with regard to Aβ level. We also examined measurement bias attributable to level of cognitive functioning and sex as positive controls. Methods: We examined 3961 cognitively normal older adults from the A4/LEARN Study. We used the MIMIC (multiple indicators, multiple causes) approach to detect measurement bias. Results: We found measurement bias with small‐to‐moderate range effect sizes in several GDS‐15 items with respect to Aβ level, cognitive functioning, and sex. There was negligible impact of measurement bias attributable to Aβ level on overall depressive symptom level. Discussion: GDS‐15 item responses are sensitive to Aβ burden, cognitive functioning, and sex over and above what would be expected given the effect of those factors on depressive symptom severity overall. However, these direct effects for GDS item measurement bias are of small magnitude and do not appreciably impact the validity of inferences about depression based on the GDS‐15.